2007
DOI: 10.1108/09593840710730545
|View full text |Cite
|
Sign up to set email alerts
|

The importance of power and ideology in communities of practice

Abstract: Purpose -The purpose of this paper is to identify and discuss some underdeveloped issues in Community of Practice theory and their practical implications for the study of the organization. Design/methodology/approach -The paper shows that, in order to achieve this goal, first the blind spots are identified (such as power issues and the relation of the community with its environment) based on a literature review. Then, a case study is presented, carried out in a large Dutch organization (referred to as the Desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…136 It is the interaction of individuals and active collaboration 137 that creates group identity as individuals create meaning through sense making. 138 Within the current study we observed this happening to some extent through specific projects, such as those that employed more interactive methods, for example improvement projects. This supports the idea that the topic or subject area around which a collaboration is focused is also important for its success.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 89%
“…136 It is the interaction of individuals and active collaboration 137 that creates group identity as individuals create meaning through sense making. 138 Within the current study we observed this happening to some extent through specific projects, such as those that employed more interactive methods, for example improvement projects. This supports the idea that the topic or subject area around which a collaboration is focused is also important for its success.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 89%
“…Although the practice of informal collaborative learning through knowledge sharing is not limited to organizational settings, a number of studies about CoPs were conducted primarily in organizational environments. Whether it was about employees of Caterpillar (Ardichvili, Page, & Wentling, 2003), coordinators for Adult Learning Councils (Gray, 2004), user interface designers (Veenswijk & Chisalita, 2007), Xerox technicians (Orr, 1996), or insurance claim processors (Wenger, 1990), these studies discussed knowledge‐sharing practices of CoPs within organizational boundaries. As noted earlier, knowledge‐sharing practices outside organizations are already occurring.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, a CoP is a network of professionals who gather for the purposes of knowledge sharing and peer-to-peer learning on a wide range of topics within the same field of practice (Wenger, 1999). A CoP provides an informal network of support for practitioners to learn best practices and share concerns with other community members (Veenswijk and Chisalita, 2007). Both online meetings among professionals just as one would in a face-to-face CoP and an information exchange in a social media group can be considered vCoP activity.…”
Section: Social Media As a Source Of Information Supportmentioning
confidence: 99%